Influence of dirt accumulation on performance of PV panels - Sulaiman, S.A. (Elsevier Ltd, 2014)
Accumulation of dirt or particles like dust, water, sand and moss on the surface of solar photovoltaic panel obstruct or distract light energy from reaching the solar cells. This is a major problem since the light obstruction materials pose as external resistances that reduce solar photovoltaic performance. The present work was performed to analyze the effects of accumulation of such dirt or particle son the output performances of solar panel. Experiments using different obstruction materials were conducted under controlled conditions using spotlights to simulate source of solar radiation. It was found that the external resistance could reduce the photovoltaic performance by up to 85. Â© 2014 Elsevier Ltd.